Pengaruh Rekondisi Poros Engkol Aux. Engine No. 1 Terhadap Kenaikan Temperature Minyak Lumas Di MT. Senipah - Bayu Putra Pratama (Meteor STIP Marunda, 2023)
Aux. Engine generator is an auxiliary machinery or generator, which functions to generate electricity. The electricity is useful for shipboard purposes such as supplying electricity pumps, electrical equipment and other machinery that uses electrical energy on board the ship. Researchers use qualitative descriptive methods, triangulation of observation results, interviews and literature studies. Using SHEL data analysis techniques, researchers identified the causal factors, impacts and efforts made related to the influence of Aux crankshaft reconditioning. Engine No.1 against the increase in L.O temperature. The results obtained from this study showed that the cause of the increase in L.O temperature Aux. Engine No.1 is caused by the wear of the crankpin bearing, with the damage it will have an impact on the looseness of the crankpin bearing components with the crankshaft so that the L.O pressure decreases and the L.O lubrication is not optimal. Efforts made to prevent this are to wait for ship spare parts with standards in accordance with the manual book and crankpin size after reconditioning, as well as carry out routine system maintenance plans.